Karakteristik Fisik dan Kimia Telur Burung Mamoa (Eulipoa Wallacei) di Pantai Uwo Uwo Kecamatan Galela Kabupaten Halmahera Utara - Yusri Sapsuha; Nur Sjafani; Nurjana Albaar; Hasriani Ishak (Jurnal Sain Veteriner, 2017)
The aim of this research was to determine physicochemical characteristics of Mamoa egg. The eggs were collected about 100 eggs from Uwo uwo beach. Physical quality was observe in Animal Husbandry laboratory, Faculty of Agricultural, Khairun University. The physical characteristics observed were measuring include weight, shape, colour of eggshell, length, diameter, egg index, albumen, yolk, weight of eggshell, haugh unit, and thickness of eggshell. The chemical characteristics consist of moisture content, protein, fat content, fiber content, ash, carbohydrate, cholesterol, and antioxidant. Data were analyzed by quantitative descriptive analysis. The result showed that physical quality of egg were weight = 97.28 g, length = 7.12 cm, diameter = 5.45 cm, index of egg = 71.89%, Percentage of yolk and albumen were 69.12% and 23.24%, haugh unit score = 68.78 and shape of egg was ovale. The chemical characteristic of egg chemical quality were protein content = 15.47%, fat content = 8.31%, carbohydrate = 25.52 %, cholesterol = 387.54 mg/100gr, and antioxidant = 49.08% dpph.